Pola Pembinaan Usia Dini pada Klub-Klub Bola Basket di Kabupaten Temanggung (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the Achievement Development and Early Childhood Development Patterns in Basketball Clubs in Temanggung Regency in 2020. This study used a descriptive quantitative research approach. The results of the study show that according to the indicators of infrastructure for achievement development are in the poor category, organizational indicators for achievement development are in the medium category, environmental indicators for achievement development are in the medium category, management indicators for achievement development are in the medium category and funding indicators for coaching achievement is in the medium category. The results showed that according to the physical indicators the majority of respondents were in the good category, and the mental aspect indicators of the majority of the respondents were in the good category. Based on the results of the study, it can be concluded that the development of achievement in basketball clubs in Temanggung Regency in 2020 consists of facilities and infrastructure that are in the less category, organizations that are in the medium category, the environment which is in the medium category, management which is in the middle category. moderate, and funding is in the medium category and the physical aspect is in the good category, the mental aspect is in the good category and the social aspect is in the good category